Psychometric properties of Improper Attitude Towards Eating Behaviour Questionnaire in Men (KBZOM) - Pawłowska, Beata; Rzeszutko, Ewa; Potembska, Emilia (Current Problems of Psychiatry, 2011)
The article presents stages of construction of Eating Disorder Questionnaire for Men (KBZOM) created by Beata Pawłowska and Zofia Stankiewicz. In the first stage, the questionnaire consisting of 90 questions was created, which described symptoms of eating disorders, characteristics of negative self-esteem and bigorexia among 22 years old men. In the next stage, factoral analysis was completed. As a result of this analysis three factors were selected: 1) Bigorexia, 2) negative self-esteem, 3) overeating and coping with emotions. Items with the lowest factorial loads and the lowest rates of specificity factor were rejected. The final version of KZPO questionnaire consists of 65 questions. Reliability coefficients for each factor are high and are as follows: for bigorexia α = 0.97, for negative body image α = 0.96, for overeating and coping with emotions α = 0.95. The selected three factors explain 62% of the total variance; the Questionnaire (KBZOM) is short, with good psychometric tool used to study the various dimensions of disordered eating attitudes in men.